Cognitive Orientation to daily Occupational Performance Approach with children with Dravet syndrome using a telerehabilitation format: A single subject study - Ianes, Patrizia Gabriella; Martini, Rose; Bertholom, Yann; Montecchi, Maria Giulia; Salvatore, Giulio; Cutrona, Costanza; Moriconi, Federica; Quintiliani, Michela; Borroni, Simona; Rega, Filomena Rita; Rosaria Chieffo, Daniela Pia; Battaglia, Domenica Immacolata (Epilepsy & behavior, 2025)
•Telerehabilitation is a feasible CO-OP Approach format for children with Dravet.•Following the CO-OP Approach, children improved performance on trained goals.•Children showed evidence of skill transfer, improving performance on untrained goals.•The CO-OP Approach seems to have a positive effect on parents’ self-efficacy. Dravet syndrome (DS) is a severe form of epilepsy that affects a child’s cognitive, language, behavioral, and physical abilities, leading to reduced adaptive functioning. Despite its impact, there is limited evidence supporting effective interventions for these children, particularly in addressing their occupational performance. To explore the effectiveness of the Cognitive Orientation to Daily Occupational Performance (CO-OP) approach in a telerehabilitation format for children with DS. A single-subject design with multiple baselines across goals was used with four children (aged 9–13 years) with DS, who received eight online CO-OP sessions. Five goals were set using the Canadian Occupational Performance Measure (COPM), three of which were targeted in the intervention. Activity performance was rated using the Performance Quality Rating Scale (PQRS) and analyzed using the 3SD band method. Children and parents rated perceived performance and satisfaction on the COPM. Secondary outcomes included parents’ sense of competency, children’s adaptive behavior, and quality of life. Significant improvements in PQRS scores were seen for 8 of the 12 trained goals and 3 of the 7 untrained (transfer) goals. COPM scores showed changes greater than 2 points in both children’s and parents’ perceived performance and satisfaction for trained and untrained goals. Improvements were also noted on the secondary measures for 3 of 4 participants. These findings provide preliminary evidence that the CO-OP approach in a telerehabilitation format improves both trained and untrained goals, with a positive effect on parent self-efficacy, adaptive functioning, and quality of life. Further research is needed to confirm these results.